3D modelling and capacity estimation of potential targets for CO2 storage in the Adriatic Sea, Italy. Issue 1 (2022) - Proietti, Giampaolo; Cvetković, Marko; Saftić, Bruno; Conti, Alessia; Romano, Valentina; Bigi, Sabina
No abstract available